Pengaruh Kompetensi, keterlibatan Kerja dan Disiplin kerja terhadap Kinerja Guru SMK Negeri 1 Bantaeng Kabupaten Bantaeng - Adiwijaya, Adiwijaya; K, Kasnaeny; Sukmawati, St. (Innovative: Journal Of Social Science Research, 2024)
Abstract This research aims to investigate and analyze the influence of competence, work engagement, and work discipline on the performance of teachers at SMK Negeri 1 Bantaeng, Bantaeng Regency. The target population for this study comprises individuals related to teacher performance, totaling 83 respondents, all of whom were included in the analysis using multiple linear regression. The results of this study indicate that all variables competence, work engagement, and work discipline have a positive and significant simultaneous effect on the performance of teachers at SMK Negeri 1 Bantaeng, Bantaeng Regency. Furthermore, it was found that the work engagement factor has the most dominant significant influence on the performance of teachers at SMK Negeri 1 Bantaeng, Bantaeng Regency. Keywords: Competence, Work Engagement, Discipline, Teacher Performance